Left sided gallbladder: A case report during laparoscopic cholecystectomy for acute cholecystitis. (2020) - Roli, Isabella; Colli, Francesco; Mullineris, Barbara; Esposito, Sofia; Piccoli, Micaela
Highlights: Left-sided gallbladder. Acute Choleystitis. Laparoscopic Cholecystectomy. Abstract: Introduction: A true left sided gallbladder (T-LSG) is a rare finding mostly discovered incidentally during laparoscopy and often associated with several anatomic anomalies; surgical approach may be challenging with an increased risk of intra-operative injuries and conversion to open. Presentation of the case: A 76 years old woman presented with acute cholecystitis. The left sided gallbladder was unexpectedly discovered as an intra-operative finding. Laparoscopic cholecystectomy was carried out using our usual trocar set-up without the need of intra-operative cholangiography or conversion to open. Discussion: LSG is reported to be associated with a higher risk of intraoperative bile duct injuries (up to 7.3%) due to anomalies of the bile duct, portal vein, and other structures. Achieving the Critical View of Safety by opening Calot's triangle is essential to avoid bile duct injuries. Conclusion: Experienced surgeons could safely approach LSG laparoscopically, also in emergency setting, without major changing in their surgical technique with limitation of diathermy use and prudent dissection of anatomical structures to avoid biliary injuries. Intra-operative cholangiography is not mandatory.